2018
DOI: 10.1002/ece3.4099
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in distinguishing climatic and anthropogenic contributions to alpine grassland variation on the Tibetan Plateau

Abstract: Quantifying the impact of climate change and human activities on grassland dynamics is an essential step for developing sustainable grassland ecosystem management strategies. However, the direction and magnitude of climate change and human activities in driving alpine grassland dynamic over the Tibetan Plateau remain under debates. Here, we systematically reviewed the relevant studies on the methods, main conclusions, and causes for the inconsistency in distinguishing the respective contribution of climatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 112 publications
1
51
0
1
Order By: Relevance
“…Quantifying the key ecosystems' dynamics controlling factors is crucial for ecological management and adaptation (Li L. et al, 2018;Wei et al, 2020). Alpine grasslands in Tibet are one of the most vulnerable biomes to human activities and climate change in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying the key ecosystems' dynamics controlling factors is crucial for ecological management and adaptation (Li L. et al, 2018;Wei et al, 2020). Alpine grasslands in Tibet are one of the most vulnerable biomes to human activities and climate change in the world.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of how ecosystem ANPP responds to climate change and human activities can help mitigate environmental damages and optimize ecosystem management (Zhou et al, 2018). A considerable volume of literature tried to identify and quantify the relative influences of climate change and human activities on ecosystem productivity with various methods (Paudel and Andersen, 2010;Erb et al, 2018;Li L. et al, 2018), such as manipulative experiments, traditional statistical analysis, and residuals-trend modeling (Li L. et al, 2018). Recently, random forest modeling, with high accuracy and robust efficiency, is increasingly being used to quantify predictors' relative importance (Gill et al, 2017;Huang and Xia, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, growing season NDVI (GNDVI) derived from GIMMS 3g exhibited a decreasing trend from 2000 to 2012, however, the GNDVI from C5 products of MODIS Terra remained showing increasing trends for the same period on the TP [23][24][25]. Moreover, these inconsistencies of vegetation changing trends might further intensify the ongoing disputes over drivers for vegetation dynamics on the TP [24][25][26][27]. Studies based on GIMMS 3g NDVI, for example, have found a positive correlation between vegetation greenness and temperature [28,29], whereas studies based on MODIS Terra-C5 NDVI argued that climate warming adversely affected vegetation growth [24].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies were mostly conducted within an individual factor perspective, e.g., road network and settlement locations. The role of human activities is becoming more and more important in influencing vegetation change [27]. Several studies even argued that anthropogenic activities were the primary contributors to changes in one-third alpine vegetation on the TP since 2000 [33,40].…”
Section: Introductionmentioning
confidence: 99%
“…The research methods mainly used the Carnegie-Ames-Stanford approach based on remote sensing [18], MODIS vegetation indexes, the random forest or random forest regression algorithm, modeling, and WorldView-2 imaging [97,98]. The research focused on the biophysical characteristics, phenological processes [12,74], and grassland management characteristics (degradation and grazing effects), and differentiated between the contributions of the influences of climate change and anthropogenic activities to NPP [99][100][101][102]. These can better predict future climate to help cope with the impact of global climate change on humans and to more quickly achieve sustainable development goals.…”
Section: Research Frontiersmentioning
confidence: 99%